2016
DOI: 10.1097/mcd.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Frame shift mutations of the ZMPSTE24 gene in two siblings with restrictive dermopathy

Abstract: Restrictive dermopathy (RD) is a rare lethal autosomal recessive genodermatosis, characterized by abnormally rigid skin with prominent superficial vasculature, erosions and epidermal hyperkeratosis, dysplastic clavicles, joint contractures, mouth fixed in the 'O' position, small pinched nose, and neonatal death. Mutations of ZMPSTE24 and LMNA genes are reported as the causes of RD, with those of ZMPSTE24 being more prevalent. Here, we report on a familial c.50delA (p.Lys17Serfs*21) mutation of the ZMPSTE24 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The exact pathogenetic mechanism of the fetal RD remains unclear, but it appears to involve a primary defect of collagen metabolism [22,23]. It is therefore suggested that RD was caused in most cases by ZMPSTE24 autosomal recessive mutations, or less frequently by LMNA autosomal-dominant mutations [24][25][26]. In the present study, we report the identification of two novel ZMPSTE24 gene Yunan Wang and Chang Liu contributed equally to this work.…”
Section: Introductionmentioning
confidence: 64%
“…The exact pathogenetic mechanism of the fetal RD remains unclear, but it appears to involve a primary defect of collagen metabolism [22,23]. It is therefore suggested that RD was caused in most cases by ZMPSTE24 autosomal recessive mutations, or less frequently by LMNA autosomal-dominant mutations [24][25][26]. In the present study, we report the identification of two novel ZMPSTE24 gene Yunan Wang and Chang Liu contributed equally to this work.…”
Section: Introductionmentioning
confidence: 64%
“…The second translation initiation site corresponds to the M13-codon of the wild type protein (see illustration in Figure 2B). Analysis of published disease causing ZMPSTE24 mutations 10,11 and expression of ZMPSTE24(insT+M13I)-GFP (Figure 2F) revealed that all other potential in-frame start codons (=methionine codons) cannot act as physiological TISs to prevent complete loss of protein function.…”
Section: Methodsmentioning
confidence: 99%
“…According to recent studies, the typical RD phenotype seems to be due to ZMPSTE24 null mutations and complete loss-of-function whereas less severe phenotypes could be associated with ZMPSTE24 haploinsufficiency or LMNA mutations (often called “RD-like phenotypes”) (Fig. 4c ) [ 97 , 98 ].…”
Section: Diseases Caused By Mutations Affecting Proteins Of the Outermentioning
confidence: 99%